Global Warming, Air Pollution and Health - Attfield, Robin (Studia Ecologiae et Bioethicae, 2023)
A new field of biomedical ethics is opening up, concerning what should be done to reduce the direct and indirect impacts of greenhouse gas emissions on human health. Some of these impacts could be described as ‘direct’, in the form of fatalities and illnesses due to the increasingly frequent heatwaves in many countries of recent years, ascribable to anthropogenic climate change. Other impacts are mediated through the air pollution that results from emissions from vehicles in the form of a cocktail of carbon oxides including carbon monoxide, nitrogen dioxide and particulates. Most of the world’s cities have streets with unsafe pollution levels, and one child’s death in Britain has been officially ascribed to air pollution (BBC 2020). This presentation aims to validate the above claims about the impacts of emissions on health, and to suggest remedies. The early phasing out of vehicles powered by internal combustion engines is the ultimate remedy for the latter set of impacts, while the urgent replacement of energy generated from fossil-fuel sources with renewable energy is the best way to remediate the former set. More immediate remedies for air pollution include restricting the use of roads and streets in urbanised areas by vehicles to bicycles and light vehicles with small engines. Medical and nursing education should include the diagnosis and treatment of pulmonary conditions resulting from increased levels of carbon oxides, nitrogen oxides and particulates. Medical and nursing practice should focus on the early identification of vulnerable adults and children at risk from air pollution, and warnings against walking, running or cycling along the most polluted thoroughfares.